2021
DOI: 10.1128/iai.00626-20
|View full text |Cite
|
Sign up to set email alerts
|

Isolate-Dependent Differences in Clinical, Pathological, and Transcriptional Profiles followingIn VitroandIn VivoInfections with Rickettsia rickettsii

Abstract: Rickettsia rickettsii, the etiological agent of Rocky Mountain spotted fever (RMSF), a life-threatening tick-borne disease that affects humans and various animal species, has been recognized in medicine and science for more than 100 years. Isolate-dependent differences in virulence of R. rickettsii have been documented for many decades; nonetheless, the specific genetic and phenotypic factors responsible for these differences have not been characterized. Using in vivo and in vitro methods, we identified multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Levin et al [ 180 ] reported that guinea pigs developed a disseminated infection when fed upon by ticks infected with R. amblyommatis . Rickettsia rickettsii has also been shown to have highly varied levels of virulence in animal models; therefore, it is not surprising that this is the case with R. amblyommatis [ 9 , 197 , 198 ]. It is also possible that these differences in observed pathogenicity in guinea pigs could be due to varied strains of R. amblyommatis being used in the experiments [ 9 ].…”
Section: Pathogenicitymentioning
confidence: 99%
“…Levin et al [ 180 ] reported that guinea pigs developed a disseminated infection when fed upon by ticks infected with R. amblyommatis . Rickettsia rickettsii has also been shown to have highly varied levels of virulence in animal models; therefore, it is not surprising that this is the case with R. amblyommatis [ 9 , 197 , 198 ]. It is also possible that these differences in observed pathogenicity in guinea pigs could be due to varied strains of R. amblyommatis being used in the experiments [ 9 ].…”
Section: Pathogenicitymentioning
confidence: 99%
“…42 Previous studies have demonstrated that SFGR manipulate vertebrate hosts to establish sufficient loads in the host cells for successful horizontal transfer. 43,44 For other obligate intracellular bacterial pathogens, burdens of bacteria within the host have been shown to be associated with disease severity. 45,46 The greater growth rate of R. parkeri in mammalian cells than that of R. amblyommatis, resulting in higher bacterial load of the pathogenic agent, may be one of the important factors contributing to increased severity of disease and transmission efficiency to tick vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Blood component copy number was determined by the PanR8 qPCR to be 55. 7 Rco and Rri whole blood separation. Whole blood was inoculated with approximately 1,800 copies/mL of either Rri or Rco and split into 3 (Rco) or 6 (Rri) 1 mL aliquots sedimented with Histopaque 1077 gradient.…”
Section: Whole Blood Sedimentationmentioning
confidence: 99%
“…Rickettsia are Gram-negative obligate intracellular bacteria that localize in the vascular endothelium and disseminate through the body via the bloodstream and lymph likely via lymphocytes, and other non-endothelial cells [4,5]. In vivo and in vitro analyses of virulence suggest that the level of circulating bacteria varies by species and strain of spotted fever group Rickettsia (SFGR) [6][7][8]. Cultivation and isolation of the illness causing bacteria enhances molecular diagnosis and allows for further characterization.…”
Section: Introductionmentioning
confidence: 99%